Hubungan antara Work Meaningfulness dengan Organizational Citizenship Behavior pada Karyawan PT. X Kota Gresik - Nada Kinanti; Meita Santi Budiani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Employees as the key holders of organizational success are expected to be able to play an active role in achieving organizational goals. This study aims to obtain information about the relationship between work meaningfulness and organizational citizenship behavior (OCB). The approach used is quantitative correlation with collection through a Google Form-based questionnaire. The psychological scale of this study is based on the theory of work meaningfulness by Andrea Veltman (2016) and OCB by Dennis W. Organ (2006). The method used is simple random sampling on 149 permanent employees with a minimum working period of 2 years and still actively working at PT. X Gresik City. A total of 30 employees were used to test the validity and reliability of the measuring instrument. Data analysis was carried out by Pearson Product Moment correlation test using IBM SPSS version 25.0. The results showed a significance value of 0.000 (p<0.05) which means that there is a positive and significant relationship between variables with a correlation coefficient of 0.782 (r=0.782). This study shows the results that the higher the work meaningfulness, the organizational citizenship behavior shown by employees will be higher, and vice versa. This research is expected to show the importance of work meaningfulness to increase employee engagement in the organization. This involvement can be realized through training, forming a positive work environment and meeting employee needs.